Madura Indigenous Communities' Local Knowledge in the Participating Planning and Budgeting Process - Sopanah, Ana; Harnovinsah, Harnovinsah; Sulistyan, Riza Bahtiar (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
This study aims to uncover the role of local wisdom in participatory planning and budgeting within Madura indigenous communities and to develop a model of local community wisdom for these processes. A qualitative ethnomethodological approach within a constructivist paradigm was employed. The results indicate that formal deliberations, such as development planning meetings, are similar to those in other regions of Indonesia. However, the Madurese indigenous people distinguish themselves by also engaging in informal deliberations through community meetings. While participatory budgeting is well-documented elsewhere, the Madurese approach uniquely incorporates community consultations as a preliminary stage. This method allows the community to articulate aspirations and formulate needs, thereby achieving local goals through a culturally grounded participatory process. Keywords:  local wisdom, participatory budgeting, planning processes